Security Enhancement in Image Watermarking Using Combined Medium Sub-Band Wavelet Approach for Copyright Protection - Balakrishnan, Sridhar (Proceedings of Engineering and Technology Innovation, 2021)
Watermarking in multimedia content has secured attractive approaches in research society since nowadays the transmission of digital content in wireless medium has been enormous. Along with the distribution of digital content, it is important to claim ownership. A non-blind detection technique is proposed in this paper. First, an original image undergoes the wavelet decomposition such as LL1, LH1, HL1, and HH2. Afterward, the medium level sub-band coefficients of the image are subject to the comfortable shares for merging. Next, one of the shares from the LH1 band is merging with another one of the shares in HL1 band. In this stage, the copyright mark is fetched into the merged sub-band coefficients. Finally, an inverse wavelet transform is applied to receive the watermarked image. To prove the authentication, the original image and the watermarked image undergo the same operation and acquire copyright information. Experimental results achieve that the proposed approach can withstand various image processing attacks.